Manajeman Peningkatan Mutu untuk Mewujudkan Pendidikan Berkualitas - Riyad, Muhamad; Ali2, Agus; Septiani, Dewi; Masyani, Khurul; Irfani, Alawiyah; Zahrotunnzibah, Asri; Dardiri, Deden; Badriah, Saidah; Abidin, Zaenal (STIT Sirojul Falah Bogor, 2022)
Every institution or institution certainly expects quality education, and everyone will certainly prefer to study or send their children to school in an institution that has good quality. Therefore, schools/educational institutions must be able to provide good service and quality to customers in order to be able to compete with other educational institutions. From various views, the indicators that the author can take are that quality education can be improved if the school has (1) students, 2) effective principal leadership, 3) good teacher performance, 4) relevant curriculum, 5) quality graduates, 6) an effective organizational culture and climate) 7) support from various parties (from the government, the community and parents of students), 8) Infrastructure that supports the learning process. management in improving the quality of education is a solution for efforts to realize the quality of education/quality education. Keywords: total quality management, educational management, quality of education, strategict management.